Literature Review of the Impact of Fintech on Financial Access in Developing Countries - Minarni, Eni; Eldon, Mokhamad (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Digital transformation in the financial sector through financial technology (fintech) has become a global phenomenon that has the potential to accelerate financial inclusion, especially in developing countries. This article aims to systematically review various academic literature and policy reports on the role and impact of fintech on financial access for communities that have previously been underserved by formal financial institutions. The method used is a literature study by reviewing various scientific journals, reports from international institutions, and relevant policy documents. The results of the study show that fintech, through services such as digital wallets, peer-to-peer (P2P) lending, and mobile-based payments, is able to overcome geographical barriers, high costs, and lack of documentation that are the main barriers to financial access in developing countries. However, challenges such as low digital literacy, inequality in technological infrastructure, and lack of comprehensive regulations are still obstacles to optimal utilization of fintech. Therefore, strong collaboration between regulators, industry players, and the community is needed to ensure that fintech innovation is truly inclusive and sustainable. This article provides important insights for policy makers, academics, and industry players in designing strategies and policies that support the growth of a healthy fintech ecosystem in developing countries.